2018
DOI: 10.1039/c8ra07251e
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and evaluation of two angiotensin-I-converting enzyme inhibitory peptides from fermented grains (Jiupei) used in Chinese Baijiu production

Abstract: Two tripeptides with ACE inhibitory activity were isolated from Jiupei (the raw material of Baijiu) distillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In this study, the main purpose was to measure the identified peptides’ (Zhang, Jiang, et al, ) antioxidant activities with ABTS, 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH), ORAC, reducing power (RP), and ferrous chelating ability (FCA) assays. The effect of protection against 2,2′‐azobis (2‐methylpropionamide)‐dihydrochloride (AAPH)‐induced oxidative damage in human hepatoma cells (HepG2 cells) was also investigated by measuring the levels of OS biomarkers [MDA, oxidized glutathione (GSSG), and glutathione (GSH)] and antioxidant enzymes (SOD, CAT, and GSH‐Px).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the main purpose was to measure the identified peptides’ (Zhang, Jiang, et al, ) antioxidant activities with ABTS, 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH), ORAC, reducing power (RP), and ferrous chelating ability (FCA) assays. The effect of protection against 2,2′‐azobis (2‐methylpropionamide)‐dihydrochloride (AAPH)‐induced oxidative damage in human hepatoma cells (HepG2 cells) was also investigated by measuring the levels of OS biomarkers [MDA, oxidized glutathione (GSSG), and glutathione (GSH)] and antioxidant enzymes (SOD, CAT, and GSH‐Px).…”
Section: Introductionmentioning
confidence: 99%
“…The extraction protocol of Jiupei protein was followed according to a previously published method . Briefly, 400 g frozen Jiuzao was smashed after dried.…”
Section: Methodsmentioning
confidence: 99%
“…The elution of JPH components with higher activity were carried on according to the previous study . Briefly, XAD‐16 resin was loaded in the chromatographic column and the column was rinsed with ultrapure water at a flow rate of 2 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations